The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.30773/pi.2019.01.21
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Transmission of Trauma: Psychiatric Evaluation of Offspring of Former “Comfort Women,” Survivors of the Japanese Military Sexual Slavery during World War II

Abstract: “Comfort women” are survivors of sexual slavery by the Imperial Japanese Army during World War II, who endured extensive trauma including massive rape and physical torture. While previous studies have been focused on the trauma of the survivors themselves, the effects of the trauma on the offspring has never been evaluated before. In this article, we reviewed the first study on the offspring of former “comfort women” and aimed to detect the evidence of transgenerational transmission of trauma. In-depth psychia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It has been reported that higher HPA axis reactivity with lower expression of 11β-HSD2 mRNA in placenta is shown by female offspring exposed to prenatal stressors, as compared with male offspring exposed to similar stressors. Thus, the differences in clinical manifestations of case A /C (female) and case B (male) in the findings of Lee et al [1] can be partly explained.…”
mentioning
confidence: 87%
See 4 more Smart Citations
“…It has been reported that higher HPA axis reactivity with lower expression of 11β-HSD2 mRNA in placenta is shown by female offspring exposed to prenatal stressors, as compared with male offspring exposed to similar stressors. Thus, the differences in clinical manifestations of case A /C (female) and case B (male) in the findings of Lee et al [1] can be partly explained.…”
mentioning
confidence: 87%
“…The article on the intergenerational transmission of trauma effects in the offspring of “comfort women” survivors by Lee et al [1], published in the March 2019 issue of Psychiatry Investigation , has yielded important findings. Because the “comfort women” survivors were exposed to extreme trauma, including rape, sexual torture, physical trauma, starvation, death threats, and witnessing of others being tortured and/or killed as Japanese military sexual slaves during the Second World War, all of them had post-traumatic stress disorder (PTSD) throughout their lifetimes and some had complex PTSD [2].…”
mentioning
confidence: 99%
See 3 more Smart Citations